Government Officially Revokes PPKM Policy: Stock Market Investment Decisions - Ali Wardhana; Ika Pratiwi Simbolon; Lilis Susilawaty; Stephanie Laurensia (Jurnal SEKURITAS (Saham, Ekonomi, Keuangan dan Investasi), 2023)
The aim of this study is to examine the effect of behavioural biases from investors on investment decision before and after government officially revokes PPKM in Indonesia. This study is quantitative research which relies on numerical data. Data used in this research are secondary data for trading volume from November 2022 until February 2023 of companies listed on LQ45. This study also examines the difference in trading volume before and after revoking of PPKM, hence this’s event study. The results showed that investors’ behaviours have significant effect to trading volume before and after government officially revokes PPKM. On average, total trading volume is higher after the announcement from the government, 92,174,703 shares before the announcement and 110,020,882 shares after the announcement. Reflecting on this amount, since many community activities were hampered when the PPKM policy was implemented, after the termination of the policy, investors become more optimistic about investing in the capital market. This study provides valuable insights into the irrational behaviour of investors in Indonesia. It is worth mentioning that trading activities in stock exchanges mostly remain an anomaly. Further investigations can be made using the other measurements of behavioral biases in the stock market.